2016
DOI: 10.3390/ijms17030370
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Broomcorn Millet (Panicum miliaceum L.) Cultivars and Landraces in China Based on Microsatellite Markers

Abstract: Broomcorn millet (Panicum miliaceum L.), one of the first domesticated crops, has been grown in Northern China for at least 10,000 years. The species is presently a minor crop, and evaluation of its genetic diversity has been very limited. In this study, we analyzed the genetic diversity of 88 accessions of broomcorn millet collected from various provinces of China. Amplification with 67 simple sequence repeat (SSR) primers revealed moderate levels of diversity in the investigated accessions. A total of 179 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 34 publications
(57 reference statements)
3
24
0
Order By: Relevance
“…Cultivars were also grouped according to the geographical regions in which they were registered, with specific varieties and their parents often placed in the same group, also similar to the findings of M’Ribu and Hilu (1994), Hu et al (2009), and Cho et al (2010). These results suggest that breeding of proso millet in specific regions has proceeded in isolation (Liu et al, 2016). Similar to Trivedi et al (2015), Liu et al (2016) observed abundant morphological variation in the Chinese accessions, but more molecular markers or different types of markers are needed to assess their genetic diversity.…”
Section: Genetics and Genomics Of Proso Milletsupporting
confidence: 61%
See 3 more Smart Citations
“…Cultivars were also grouped according to the geographical regions in which they were registered, with specific varieties and their parents often placed in the same group, also similar to the findings of M’Ribu and Hilu (1994), Hu et al (2009), and Cho et al (2010). These results suggest that breeding of proso millet in specific regions has proceeded in isolation (Liu et al, 2016). Similar to Trivedi et al (2015), Liu et al (2016) observed abundant morphological variation in the Chinese accessions, but more molecular markers or different types of markers are needed to assess their genetic diversity.…”
Section: Genetics and Genomics Of Proso Milletsupporting
confidence: 61%
“…These results suggest that breeding of proso millet in specific regions has proceeded in isolation (Liu et al, 2016). Similar to Trivedi et al (2015), Liu et al (2016) observed abundant morphological variation in the Chinese accessions, but more molecular markers or different types of markers are needed to assess their genetic diversity. These Chinese gene pools could also be valuable to future proso millet breeding programs since some accessions and ecotypes could be suitable to particular regions in the PNW.…”
Section: Genetics and Genomics Of Proso Milletmentioning
confidence: 93%
See 2 more Smart Citations
“…SSR markers have proven to be simple, useful, and reliable for germplasm identification, genetic diversity studies, linkage map construction, and molecular marker-assisted selection in breeding [31,32,33,34,35]. Until now, only 33 useful SSR markers have been developed for A. bisporus [36].…”
Section: Discussionmentioning
confidence: 99%